2020
DOI: 10.3390/acoustics2020020
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Low Frequency Noises of On-Shore Wind Turbines

Abstract: The expansion of renewable energy usage is one of the major social tasks in Europe and therefore requires acceptance and support from the population. In the case of onshore wind turbines, the complaints of local residents are often interpreted as infrasound disturbances conceivably caused by wind turbine operation. To improve the acceptance for wind energy projects, national standards and regulations need to incorporate such low frequency effects. This contribution presents long-term acoustic measurement data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…It has been shown that the emitted low-frequency sound power of the tower depends on the rotational speed and on the wind speed, while the emissions of the blades are additionally influenced by the turbulence intensity. These numerical results match the findings from free-field measurements by Blumendeller et al, 15 who observed the same correlation between rotational speed and low-frequency sound emission, and by D'Amico et al, 17 who identified wind speed as well as turbulence intensity as dominant influencing factors. A yawed inflow is negligible for the sound emissions as long as it is not so large that the operating mode changes.…”
Section: Sound Power Levelsupporting
confidence: 88%
See 1 more Smart Citation
“…It has been shown that the emitted low-frequency sound power of the tower depends on the rotational speed and on the wind speed, while the emissions of the blades are additionally influenced by the turbulence intensity. These numerical results match the findings from free-field measurements by Blumendeller et al, 15 who observed the same correlation between rotational speed and low-frequency sound emission, and by D'Amico et al, 17 who identified wind speed as well as turbulence intensity as dominant influencing factors. A yawed inflow is negligible for the sound emissions as long as it is not so large that the operating mode changes.…”
Section: Sound Power Levelsupporting
confidence: 88%
“…Low-frequency noise has a smaller dissipation factor in air and can travel farther than high-frequency noise. This was found in measurements 14,15 on the infrasound propagation for distance up to 10 km, especially for stable atmospheric conditions. Hence, the extent to which such low-frequency emissions can be perceived by humans living in the vicinity of the WT is the subject of intensive research and is sometimes controversially discussed.…”
Section: Low-frequency Noise Of Wind Turbinesmentioning
confidence: 57%
“…In previous investigations, the BPF and its harmonics in the infrasonic frequency range could be clearly assigned to the WT operation [16]. Following the publication by Zajamšek et al [20], the 4th harmonic of the BPF is detected to identify infrasound occurrences.…”
Section: Data Evaluationmentioning
confidence: 97%
“…Additionally meteorological measurements of wind speed and direction (with a 23 Hz sampling frequency), humidity, temperature and pressure (with a 10 Hz sampling frequency) were conducted at the WF site with a 10 m high met mast. More detailed information concerning the instrumentation, measurements, locations with surrounding conditions and schematics of the indoor measurement set-up can be found in [16,17].…”
Section: Measuring Location Setup and Periodsmentioning
confidence: 99%
“…To date, various attempts have been made to determine noise levels at audible and infrasound frequencies. Blumendeller et al 4 used measurement microphones with two windscreen configurations, one conforming to IEC 61400-11 5 and a second using a windscreen box buried flush to the ground surface. Additionally, meteorological data were recorded near the measurement site.…”
Section: Introductionmentioning
confidence: 99%